2009
DOI: 10.1897/08-001.1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and behavioral effects of diazinon exposure in hybrid striped bass

Abstract: The effects of environmental stimuli on biochemical processes may influence behavior. Environmental contaminants that alter behavior can have major impacts on populations as well as community structures by changing species' interactions. One important behavior is the ability to capture prey. We hypothesized that sublethal exposure to diazinon, an organophosphate pesticide, may lead to feeding behavior abnormalities in hybrid striped bass (Morone saxatilis x M. chrysops) through inhibition of brain acetylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, Beauvais et al (Beauvais et al, 2001) correlated decreased swimming speed of rainbow trout to increased AChE inhibition following 24 or 96 hour exposures, or 96 h exposure and a 48 h recovery period, to carbaryl or cadmium chloride. Other studies have also concluded that the severity of behavioral alterations by organophosphates stem from duration, compound and concentration specific AChE inhibition because decreases in fish locomotor activity levels were observed at higher treatment levels (Gaworecki et al, 2009). Because the type of behavioral responses may vary with timing and concentration, modulations in swimming speed were assessed (Ingebretson and Masino, 2013); we identified increased swimming bursts of larvae exposed to DZN at the highest doses but not at lower treatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Beauvais et al (Beauvais et al, 2001) correlated decreased swimming speed of rainbow trout to increased AChE inhibition following 24 or 96 hour exposures, or 96 h exposure and a 48 h recovery period, to carbaryl or cadmium chloride. Other studies have also concluded that the severity of behavioral alterations by organophosphates stem from duration, compound and concentration specific AChE inhibition because decreases in fish locomotor activity levels were observed at higher treatment levels (Gaworecki et al, 2009). Because the type of behavioral responses may vary with timing and concentration, modulations in swimming speed were assessed (Ingebretson and Masino, 2013); we identified increased swimming bursts of larvae exposed to DZN at the highest doses but not at lower treatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral assays followed procedures from previous studies in our laboratory [14,15,19]. Briefly, 3-d after the final individual training, the day 0 feeding event was quantified before the addition of antidepressant mixtures.…”
Section: Experimental Designmentioning
confidence: 99%
“…These effects may increase the probability of ecological death, or death by normal ecological processes such as predation, starvation, disease, or myriad other causes [7,8]. Several studies of fishes have determined that numerous pesticides may do just that, by altering locomotory activity [9,10] or by impairing the ability to detect predator scent [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%